Drafting a Business Plan for Brass Instrument Reparation named BrassON in Yogyakarta - Rico Saktiawan Jang Jaya (Eastasouth Institute, 2022)
The purpose of this research is to draft a business plan for brass instrument reparation named BrassON. The brass instruments reparation business is a business that can fix any damage to any type of brass instrument. In Yogyakarta, there is no business that focuses on brass instrument reparation. Therefore, it requires a business plan for brass instruments reparation so that the business can run well. Before drafting the business plan for brass instrument reparation BrassON, a competition analysis of the industry is conducted to know the market situation for brass instrument reparation in Yogyakarta. The formulation of the mission, vision, marketing plan, operation plan, human resource plan, and financial plan of brass instruments reparation business adapted to market conditions brass instruments reparation. Based on data obtained from questionnaires, there are positive responses and interest from potential customers. BrassON presence in Yogyakarta as reparations services of brass instruments is expected to be a solution to the problem is not the presence of service brass instruments reparation in Yogyakarta. The initial investment spending used for the establishment BrassON is Rp 423.554.000. Net Present Value of Rp 145.998.845, Internal Rate of Return of 24 percent, and a payback period of 2.2 years. Based on financial analysis, the brass instrument reparations business BrassON is eligible to run.